SIGN, SYMBOL, EMBLEM: CONCEPTUAL DIFFERENTIATION - Andrei V. BABAITSEV (Advanced Engineering Research, 2010)
The basic semiotic terms – sign, symbol, emblem – are analyzed. Generalization of the existing notions allows to state that signs are things, objects, or phenomena which denote other  things, objects, or phenomena. Symbol can be considered a variety of sign, it is socially significant, emotionally expressive, and polysemous. Emblem is a  variety of sign with great semantic substantiation.